Impact of wind-induced resuspension on urban air quality: a CFD study with air quality data comparison - Linda, Jakub; Hasečič, Amra; Pospíšil, Jiří; Kudela, Libor; Brzezina, Jáchym (NATURE PORTFOLIO, 2025)
Wind-induced particulate matter (PM) resuspension is an increasingly recognized contributor to urban air pollution. A CFD model of 2D street canyon geometry was developed that can replicate the process of resuspension. Model created the wind speed vs concentration increase due to resuspension relationship and its key properties: threshold wind speed causing resuspension (TWSR) and concentration increase. At least 8.75 m/s in 10 m height inlet wind speed before street canyons was needed to start the resuspension, leading to PM10 concentrations often exceeding 1 mu g/m(3), with peak values reaching as high as 3 mu g/m(3). The model can predict the behavior of resuspension well, but it cannot capture all the factors acting in the real environment to match precisely the air quality data. Silt load remains the greatest unknown factor in determining the overall magnitude of resuspension, with observed increases in PM10 concentrations up to 6 mu g/m(3) in air quality data.

Wind-induced particulate matter (PM) resuspension is an increasingly recognized contributor to urban air pollution. A CFD model of 2D street canyon geometry was developed that can replicate the process of resuspension. Model created the wind speed vs concentration increase due to resuspension relationship and its key properties: threshold wind speed causing resuspension (TWSR) and concentration increase. At least 8.75 m/s in 10 m height inlet wind speed before street canyons was needed to start the resuspension, leading to PM10 concentrations often exceeding 1 mu g/m(3), with peak values reaching as high as 3 mu g/m(3). The model can predict the behavior of resuspension well, but it cannot capture all the factors acting in the real environment to match precisely the air quality data. Silt load remains the greatest unknown factor in determining the overall magnitude of resuspension, with observed increases in PM10 concentrations up to 6 mu g/m(3) in air quality data.
Impact of wind-induced resuspension on urban air quality: a CFD study with air quality data comparison
Keywords: Resuspension; CFD; model; PM; particles; validation; Resuspension; CFD; model; PM; particles; validation